Sources of cognitive cost in scalar implicature processing: A review - Khorsheed, Ahmed; Price, Jessica; van Tiel, Bob (Frontiers in Communication, 2022)
Research in Experimental Pragmatics has shown that deriving scalar implicatures involves effort and processing costs. This finding was robust and replicated across a wide variety of testing techniques, logical terms, populations, and languages. However, a question that remains disputed in the literature is whether this observed processing cost is a product of the inferential process itself or other logical properties whose computation taxes cognitive resources independently of the inferential mechanism. This paper has two objectives: one is to review the previous experimental work on scalar implicatures and how it evolved in the literature, and the other is to discuss possible factors that render computing scalar implicatures cognitively effortful. Implications and directions for future research are provided.